A Decision Tool for the Valorization of Wood Waste - Pazzaglia Aron; Castellani Beatrice (Environmental and Climate Technologies, 2023)
Wood is an increasingly demanded biomaterial used in many industries, including construction, materials, furniture, packaging and energy production. Consumption trend indicates a significant increase in wood waste production, which could potentially be harnessed in various processes. In Europe, about 53 % of wood waste is incinerated while the 46 % is recycled. In Italy, almost the 95 % of wood waste is used in the production of chipboard and particleboard. There are many other processes available for enhancing wood recycling, but it is crucial to understand how to treat wood waste, depending on its source matrix. Wood waste is a heterogeneous material that may contain contaminants, pollutants and additives. Therefore, effective wood waste management relies on the analysis of its material composition, which provides valuable insights for waste management strategies. To address this need, a decision tool (DT) has been proposed for determining the destiny of wood waste based on its chemical composition. The DT provides quick recommendations by categorizing wood waste into four quality grades, primarily based on pollutant analysis. It assesses cellulose, lignin, hemicellulose content, and Lower Heating Value (LHV) to suggest recycling or incineration options for wood waste. Subsequently, this paper provides a brief overview of wood waste utilization. Finally, a case study is presented in which the DT was applied to wood waste obtained from a local waste management company in Perugia, Italy.